March 4th, 1999 : the recognition-primed decision hypothesis - Avelino, Taísa Araujo (2007)
On March 4, 1999, the newly appointed President of the Brazilian Central Bank, Mr Armínio Fraga, raised interest rates to a staggering 45% per annum. The objective of that decision was to keep foreign investors assets in Brazil, and prevent the country from default. At the time, Brazil suffered frem an enormously intense crisis of confidence, and fears of such default were widespread. Mr Fraga was walking a very fine line when making that decision, for it could bring forth unintended effects: the market, already concerned about Brazil's sustainability, could perceive the increased rate as an irreversible step towards the abyss inevitable default. Economic theory postulates the rational actor model as the driving force behind economic decision-making. The objective of this thesis is to present and discuss the hypothesis that this particular decision, and by extension many others, are better explained threugh the recognition-primed decision mode!.